The Global Context of Democracy in the Twenty-First Century: An Heruistic Discourse - Irabor, Paul Akere; Isinkaye, Kehinde Abiodun (NIU Journal of Humanities; Vol 9 No 3 (2024): NIU Journal of Humanities, Vol. 9 No. 3, September 2024, 2024)
The paper assesses the globalization of democracy in the twenty-first century. It identifies factors and processes that have enhanced the global spread of democracy in the twenty-first century. Such factors include globalization of democratic principles, the growth of democratic development institutions, the growth of international civil society organizations, the roles of the international press among others. It identifies challenges facing the process as consisting of the spread of global inequality, the illiberal domination of power by hegemonic forces in the international organization. It concludes that through adoption of open and transparent government by states in the contemporary period, frustration of forceful take-over of power by the military authorities, welfare promotion and enforcement of international human right laws democratic development will be enhanced in global system in the twenty-first century. Keywords: Global. Globalization. Democracy. Democratic Development, Twenty-First Century.